Pengaruh Penerapan Teknologi Informasi Pembuatan Aplikasi Raport Berbasis Microsoft Excel Terhadap Kemampu-an Tenaga Pengajar SMP Bina Bangsa Mandiri Di Gunung Putri Bogor - Senna Hendrian; Siti Julaeha; M. Ardiansyah (Yayasan Darussalam Bengkulu, 2025)
The rapid development of information technology in the digital world has given birth to various types of activities based on the use of technology in processing value data. The world of education is required to be able to keep up with the rapid and dynamic development of information technology in order to improve knowledge and the quality of human resources so that information technology can be utilized optimally. Processing student value data that contains chronological and updatable information. Microsoft Excel or Microsoft Office Excel is a spreadsheet application program created and distributed by Microsoft Corporation that can be run on Microsoft Windows and Mac OS. Making report cards manually will take a long time and a lot of energy, especially in schools that have a very large number of students. Therefore, here we will discuss the Techniques for Making and Managing Microsoft Excel-Based Report Card Applications. By using the VLOOKUP and HLOOKUP formulas, these two functions are functions in Microsoft Excel that more or less function to search or view data from a table vertically and horizontally. Thus, through this community service program activity, the aim is to provide appropriate basic knowledge to the teaching staff of Bina Bangsa Mandiri Middle School so that in the future the teaching staff in the process of processing student grade data can continue to be developed through the knowledge they have.